2016
DOI: 10.1016/j.oraloncology.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of 701 published cases of sinonasal neuroendocrine carcinoma: The importance of differentiation grade in determining treatment strategy

Abstract: The aim of this meta-analysis was to provide treatment guidelines for sinonasal neuroendocrine carcinoma (SNC) by combining all available data in the literature. A literature search for all studies concerning SNC was performed against the MEDLINE and EMBASE databases. Available clinical data was normalized, pooled, and statistically analyzed. A total of 701 cases of SNC were available for analysis, comprising 127 well or moderately differentiated sinonasal neuroendocrine carcinomas (SNEC), 459 sinonasal undiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 145 publications
7
74
2
6
Order By: Relevance
“…More specifically, we found no prognostic difference between surgical approach or CRT as locoregional curative therapy. This is not in line with the literature data, [31][32][33] in which trimodality seems to be associated with better outcome in locoregional advanced cases. However, one should always consider the biases of treatment selection, which prompted a nonsurgical approach in diseases obtaining a favorable response to IC, thus bearing a better prognosis as recently reported by a retrospective U.S. series of SNUC.…”
Section: Discussioncontrasting
confidence: 92%
“…More specifically, we found no prognostic difference between surgical approach or CRT as locoregional curative therapy. This is not in line with the literature data, [31][32][33] in which trimodality seems to be associated with better outcome in locoregional advanced cases. However, one should always consider the biases of treatment selection, which prompted a nonsurgical approach in diseases obtaining a favorable response to IC, thus bearing a better prognosis as recently reported by a retrospective U.S. series of SNUC.…”
Section: Discussioncontrasting
confidence: 92%
“…This study found a 5-year disease-specific survival of 46% for these 115 patients with sinonasal small cell carcinoma. The authors found a non-significant trend for improved disease-specific survival with the use of surgery, however, they did not stratify patients by stage [22]. In our subgroup analysis no survival benefit was found with the addition of surgery to radiotherapy and chemotherapy (p=0.96) in locally advanced sinonasal small cell carcinomas.…”
Section: Discussioncontrasting
confidence: 55%
“…The majority of these paranasal and nasal cavity tumors presented as locally advanced cancers. The other largest series examining sinonasal small cell carcinomas, published by van der Laa et al, included a cohort of 115 patients obtained from a meta-analysis of 701 published studies[22]. This study found a 5-year disease-specific survival of 46% for these 115 patients with sinonasal small cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Both NEC and SNUC often present late with a poor outcome. However, 5‐year survival of NEC is considerably better than that of SNUC (70.2% vs 35.9%) . Frequently, the presenting complaint will include unilateral nasal obstruction, headache, and facial pain.…”
Section: Sinonasal Malignanciesmentioning
confidence: 99%
“…The 4 largest studies were Kuo et al., van der Laan et al., Reiersen et al., and Xu et al . Kuo et al .…”
Section: Sinonasal Malignanciesmentioning
confidence: 99%